Retina - Ryan, Stephen J; Wilkinson, C. P; Hengst, Timothy C (Mosby, 2001)
Univ. of Southern California, Los Angeles. A three-volume set of references for retinal specialists, clinicians and scientists, summarizing all current knowledge about the retina. Topics covered include molecular biology and genetics, pathobiologic features of disease states, and ultrasonography. Previous edition: c1994. More than 3800 illustrations.
Keywords: Retinoblastoma; Retinal Diseases; retina; oftalmologie; retinitida; Retina; nemoci retiny; Retinitis; retinoblastom; CHORIOIDEA - NÁDORY